Antimicrobial susceptibility pattern of bacterial isolates from wound infection and their sensitivity to antibiotic agents at super specialty hospital, Amravati city, India - Sawdekar, Hrishikesh; Sawdekar, Radha; Wasnik, Vinod R. (International Journal of Research in Medical Sciences, 2017)
Background: Wound infection is one of the health problems that is caused and aggravated by the invasion of pathogenic organisms. Information on local pathogens and sensitivity to antimicrobial agent is crucial for successful treatment of wounds. So the present study was conducted to determine antimicrobial susceptibility pattern of bacterial isolates from wound infection and their sensitivity to antimicrobial agents. Methods: A retrospective study was conducted among patients with wound infection in Suyash super speciality hospital, from January 2012 to December 2013. Wound swab was collected using sterile cotton swabs and processed for bacterial isolation and susceptibility testing to Systemic antimicrobial agents. Results: In this study 78 bacterial isolates were recovered from 258 specimens showing an isolation rate of 31.2%. The predominant bacteria isolated from wounds were gram positive staphylococci 36 (46.2%), followed by gram negative streptococci 18 (23.1%) gram negative pseudomonas 12 (15.4 %) and gram negative proteus 8 (10.4%). The gram positive and gram negative bacteria constituted 68 (87.2%) and 10 (12.8%) of bacterial isolates; respectively. Conclusion: In the present study most of the pathogens isolated from wound isolates showed high rate of resistance to most commonly used newer antibiotics used to treat bacterial infections. Therefore, rational use of antibiotics should be practiced.